Contoured Urbanism: People, Property and Infrastructures in the Indian Himalayas. (November 2016) - Negi, Rohit; Thakur, Kesang; Ali, Syed Shoaib
The broad success of development initiatives and ensuing material prosperity in rural areas of the Indian Himalayas have seen an increasing number of families route their increased surpluses to nearby urban areas in search of speculative footholds. Yet, the region continues to be viewed as essentially rural by policy and academic literatures. This article critiques this association by focusing on social-spatial change in the town of Banjar in the Kullu district of Himachal Pradesh. We turn our attention to the stories of property and infrastructures that connect households, contractors, workers and materials, as well as the collectives that emerge or are reconfigured alongside these built environments. The article shows how upward mobility is accompanied by new susceptibilities, how an unlikely and understudied set of agents drives urban change in the absence of formal planning and how inherited hierarchies are being renegotiated through everyday practices to produce what we call 'contoured urbanism', or the uneven but geographically situated form of urbanisation in parts of the Himalayan region. The article makes the case for critical urban research as a productive entry point into debates on regional futures.